Springback Optimization of Dissimilar Thickness AA6061-T6 Blank Joint with Double Butt-Lap (DBL) Using Taguchi Method and ANOVA - Hussin, Amer Isyraqi; Abdullah, Ahmad Baharuddin (International Journal of Integrated Engineering, 2024)
This study focuses on investigating the effect of welding parameters, specifically spindle speed, feed rate, and tool tilt angle, on the springback of double-butt lap joints blank. To optimise springback of friction stir welded AA6061-T6 blanks with different thicknesses, a Taguchi L9 orthogonal design experiment was utilized. The responses of springback from lines perpendicular and parallel to the welding line were observed, and the optimal parameter combination for each type of springback was determined. Analysis of Variance (ANOVA) revealed that the tilt angle contributed the most to springback (parallel to the weld line) with 50.43%, while the spindle speed contributed the most to springback (perpendicular to the weld line) with 52.53%. Through confirmation testing, the optimal FSW parameters were validated.